Analysis of the Implementation of the TPACK-Based Problem-Based Learning Model on Students’ Critical Thinking Skills in Flat Shape Material in Grade 2 of SD Negeri Laweyan Surakarta - Clara Karunia; Ema Butsi Prihastari; Mukhlis Mustofa (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze in depth the implementation of the Problem Based Learning (PBL) model based on Technological Pedagogical and Content Knowledge (TPACK) and its influence on the critical thinking skills of second-grade students at SD Negeri Laweyan Surakarta. This research employed a descriptive qualitative approach involving three second-grade students as research subjects. Data collection techniques included observation, interviews, and documentation, with data obtained from both primary and secondary sources. The validity of the data was ensured through source triangulation and technique triangulation. Data analysis was carried out through several stages: data collection, data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the TPACK-based PBL model can foster students’ critical thinking skills in solving problems related to two-dimensional shapes, although the overall level remained moderate. Students in the high category demonstrated accurate understanding and problem solving, while those in the moderate category were able to answer correctly though only on certain types of questions. Students in the low category experienced difficulties in understanding and solving problems. Several obstacles identified during the implementation process included limited instructional time, differences in students' cognitive abilities, and difficulties in recalling and expressing the material that had been learned.